Douglas-fir (Pseudotsuga menziesii (Mirb.) Franco) in Europe: an overview of management practices - Nicolescu, Valeriu-Norocel; Mason, William L.; Bastien, Jean-Charles; Vor, Torsten; Petkova, Krasimira; Podrázský, Vilém; Đodan, Martina; Perić, Sanja; La Porta, Nicola; Brus, Robert; Andrašev, Siniša; Slávik, Martin; et al. (Springer Science and Business Media LLC, 2023)
AbstractDouglas-fir (Pseudotsuga menziesii(Mirb.) Franco), one of the most commercially important tree species in western North America and one of the most valuable timber trees worldwide, was introduced to Europe in 1827. It became a major species for afforestation in Western Europe after WWII, currently grows in 35 countries on over 0.83 million ha and is one of the most widespread non-native tree species across the continent. A lower sensitivity to drought makes Douglas-fir a potential alternative to the more drought-sensitive Norway spruce so its importance in Europe is expected to increase in the future. It is one of the fastest growing conifer species cultivated in Europe, with the largest reported dimensions of 2.3 m in diameter and 67.5 m in height. Pure stands have high productivity (up to 20 m3 ha−1a−1) and production (over 1000 m3 ha−1). The species is generally regenerated by planting (initial stocking density from less than 1000 seedlings ha−1to more than 4000 ha−1), using seedlings of European provenance derived from seed orchards or certified seed stands. As the range of end-uses of its wood is very wide, the rotation period of Douglas-fir is highly variable and ranges between 40 and 120 years. When the production of large-sized, knot-free timber is targeted, thinnings are always coupled with pruning up to 6 m. There is an increasing interest in growing Douglas-fir in mixtures and managing stands through close-to-nature silviculture, but the species’ intermediate shade tolerance means that it is best managed through group selection or shelterwood systems.
Keywords: podnebne spremembe; rast in donos; growth and yield; timber; Douglas-fir; Growth and yield; ekološke zahteve; Timber; Ecological requirements; climate change; Climate change; Settore AGR/03 - ARBORICOLTURA GENERALE E COLTIVAZIONI ARBOREE; ecological requirements; duglazija; info:eu-repo/classification/udc/630*1; 15. Life on land